1993
DOI: 10.4319/lo.1993.38.7.1500
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of riverine flooding for seston and theperiphyton of floating meadows in an Amazon floodplain lake

Abstract: Algal biomass and the chemical composition of seston and floating meadow periphyton were measured in an Amazon floodplain lake during a period of channelized river inflow and a period of overbank flow. During both periods, sedimentation of riverine particulates and loss of dissolved nutrients created strong spatial chemical gradients from the river onto the floodplain which were stable for months at a time. The molar N : P of dissolved inorganic nutrients supplied by river water was very low (NO, + NH,+ : SRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 35 publications
2
42
0
1
Order By: Relevance
“…The water temperature didn't influence anything because the annual variation of this variable is very small. Several previous studies also documented periphyton responses to these conditions in tropical floodplain lakes in the Amazon (Engle and Melack 1993;Putz 1997;França et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water temperature didn't influence anything because the annual variation of this variable is very small. Several previous studies also documented periphyton responses to these conditions in tropical floodplain lakes in the Amazon (Engle and Melack 1993;Putz 1997;França et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, colonization and succession of periphytic algal communities in Amazonian shallow lakes is little known. Previous research in the Amazon floodplain has shown the influences of riverine flooding on structure, nutrient status and productivity of periphyton, but did not examine the successional process (Engle and Melack 1993;Putz 1997;França et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…By cellular N determinations in the periphyton, BIGGS (1995) suggests that N is the most limiting nutrient for periphyton production in the majority of the rivers of New Zealand, since N/P ratios smaller than 10 were found. ENGLE and MELACK (1993), determining the contents of organic nutrients in the periphyton on macrophyte communities on the floating cushions of Lake Calado (Amazon), found ratios of C:N:P (atom) from 65:7:1 (February) to 145: 16:1 (April). Comparing that to periphyton on E. polystachya of the lagoon in the Paranapanema River, it was observed that the periphyton presents a greater quantity of C. The difference may be due to the species composition and to the composition of suspended sediments.…”
Section: Resultsmentioning
confidence: 99%
“…The periphytic composition depends on the nature and quality of the substrata as well as on the water's trophic state, and its occurrence is controlled by the water's physical and chemical factors (PIECZYNSKA, 1990). The periphyton is also characterized by its great ability to respond to environmental changes and to nutrient availability in the most varying aquatic ecosystems (STOCKNER and ARMSTRONG, 1971 ;Ho, 1979 ;CATTANEO and KALFF, 1980;SAND-JENSEN, 1983;RIBER and WETZEL, 1987;ENGLE and MELACK, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the effect of enrichment with N and P on attached algae (periphyton), either in biomass response (Cerrao et al, 1991;Engle and Melack, 1993;Mendes and Barbosa, 2002;França et al, 2009;Oliveira et al, 2010), or on the community structure approaches (Murakami and Rodrigues, 2009;Bicudo, 2009, 2010) are still scarce. Thus, this study broaden the understanding of the influence of concentration of nutrients in the structure of algae at the bottom of mesocosms artificially enriched with individual or combined actions of N and P.…”
Section: Introductionmentioning
confidence: 99%